Constructing institutional performance: a multi-level framing perspective on performance measurement and management. Issue 4 (7th June 2019) - Modell, Sven
Abstract : Research on performance measurement and management (PMM) informed by institutional theory has proliferated over the past two decades. Much of this research has concentrated on the institutional effects on organisational PMM practices and their consequences for organisational behaviour and has only recently started to pay more focussed attention to the effects of such practices on the construction of the very conceptions of performance that come to dominate institutional fields. To further integrative theory development, I pull these strands of research together into an analytical framework pivoting on the concept of institutional performance . Institutional performance is defined as the socially constructed conceptions of organisational performance that become firmly institutionalised as legitimate aspects of achievement in institutional fields. Adopting a multi-level framing perspective, I develop a set of research propositions reflecting how contradictory PMM practices, emerging in response to the institutional complexity attributable to heterogeneous and competing constituency demands, shape such conceptions of performance and how this contributes to reducing or reinforcing institutional complexity over time. I discuss the implications of applying this framework in empirical research and the contributions to institutional research on PMM as well as institutional theory, more generally, that may emerge from such research.